Study of Class IV Arabic Textbooks at Madrasah Ibtidaiah: Curriculum and Content Perspectives - Hakiki Rikza Irnaini Al Badri; Afifah Shofia Faradisa; Muhammad Farhan; Slamet Daroini (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
In a research study that researchers carried out regarding the study of Arabic textbooks for class IV Madrasah Ibtidaiah by